Beyond dropping out of school: Importance attributed to the completion of secondary education in four Chilean educational communities. - Mendoza Lira, Michelle (2023)
Various organizations and countries have made it a priority to encourage children and young people to complete their secondary education, in pursuit of equity. However, education's value is, at least, questionable. This is because it is not a guarantor of opportunities, even with the current advances in public policies to ensure access and continuity of education for all. Due to this, approaching schools and studying the importance of education is fundamental. The following qualitative research sought to analyze the importance given by four public schools in Valparaíso (Chile) to the completion of fourth grade (the last level of secondary education in this country). In each school, the management team, teachers, support professionals, students, and their families were interviewed. The information was analyzed using content analysis. The findings revealed that graduating from high school is transcendental because (1) it develops and mobilizes skills, (2) it improves job opportunities, (3) it favors access to higher education, (4) it allows the elaboration of a happy life project and (5) it constitutes a source of personal self-realization. These reasons, taken together, show that education is still perceived as a resource for equity and social inclusion.